Micro-shear bond strength of composite to deep dentin by using mild and ultra-mild universal adhesives - Zahra Raji; Mahtab Hosseini; Mehrdad Kazemian (Wolters Kluwer Medknow Publications, 2022)
Background: Considering the increasing demand for tooth-colored restorations, this study sought to assess the micro-shear bond strength (μSBS) of composite to deep dentin by using mild and ultra-mild universal adhesives. Materials and Methods: This in vitro, experimental study evaluated 75 sound third molar teeth randomized into five groups (n = 15) of Clearfil self-etch (SE) Bond (control), Tokuyama Universal Bond (TUB), and All-Bond Universal (ABU) in etch and rinse (E and R) and SE modes. The occlusal surfaces of the teeth were trimmed to expose deep dentin at 0.5 mm distance from the pulp chamber. Adhesives were applied on the dentin surface according to the manufacturers' instructions, and Z350XT composite cylinders were bonded to dentin using Tygon tubes (0.9 mm internal diameter, 2 mm height). After incubation at 37°C and 100% humidity for 24 h, the teeth underwent μSBS test in a universal testing machine. The mode of failure was also determined under a stereomicroscope. Analysis of variance, Bonferroni test, and Fisher's exact test were applied for data analysis (alpha = 0.05). Results: TUB in E and R mode (13.78 MPa) and ABU in SE mode (7.85 MPa) yielded the maximum and minimum μSBS values, respectively. No significant difference was noted in μSBS of tested universal adhesives in E and R and SE modes to deep dentin (P > 0.05). TUB yielded significantly higher μSBS than ABU (P < 0.05). No significant difference was noted in mode of failure of the groups (P > 0.05). Conclusion: Type of adhesive affected the μSBS but etching mode of universal adhesives had no significant effect on their μSBS to deep dentin.